Review on Vocabulary Teaching Strategies: Study Case: Effect of Learners’ Lexical Recall - M Bambang Purwanto; Despita Despita (Journal of English Education, Literature and Linguistics, 2022)
This study's goal was to contrast the results of of various vocabulary teaching methods, such as using context, dictionary definitions, and synonyms to teach vocabulary, on both transient and persistent vocabulary memory. Three groups of 90 intermediate EFL students were chosen at random and divided into: context, definition, and synonyms (thirty learners in each group). They received instruction in 30 vocabulary words over the course of two sessions. Two post-tests were administered, the first four weeks after the lesson and the second eight weeks later, to gauge student retention of vocabulary words. One-way ANOVA was used to evaluate the results. When compared to the other two approaches, the context method outperformed them in both postponed tests, according to the data. The study's conclusions have pedagogical ramifications for EFL instructors, students, syllabus designers, content creators, and language test creators. The study's findings also offer useful details on the best method for teaching vocabulary that results in longer-lasting retention of L2 terms.